Buyang Huanwu Decoction attenuates H(2)O(2)-induced apoptosis by inhibiting reactive oxygen species-mediated mitochondrial dysfunction pathway in human umbilical vein endothelial cells - Shen, Jian (BMC Complement Altern Med, 2016)
BACKGROUND: Apoptosis of endothelial cells caused by reactive oxygen species plays an important role in ischemia/reperfusion injury after cerebral infarction. Buyang Huanwu Decoction (BYHWD) has been used to treat stroke and stroke-induced disability, however, the mechanism for this treatment remains unknown. In this study, we investigated whether BYHWD can protect human umbilical vein endothelial cells (HUVECs) from H(2)O(2)-induced apoptosis and explored the underlying mechanisms. METHODS: To investigate the effect of BYHWD on the apoptosis of HUVECs, we established a H(2)O(2)-induced oxidative stress model and detected apoptosis by Hoechst 33342 and propidium iodide staining. JC-1 and DCFH-DA assays,western blotting and electron microscopy were used to examine the mechanism of BYHWD on apoptosis. RESULTS: Pretreatment with BYHWD significantly inhibited H(2)O(2)-induced apoptosis and protein caspase-3 expression in a concentration-dependent manner. In addition, BYHWD reduced reactive oxygen species production and promoted endogenous antioxidant defenses. Furthermore, loss of mitochondrial membrane potential and structural disruption of mitochondria were both rescued by BYHWD. CONCLUSIONS: BYHWD protects HUVECs from H(2)O(2)-induced apoptosis by inhibiting oxidative stress damage and mitochondrial dysfunction. These findings indicate that BYHWD is a promising treatment for cerebral ischemia diseases.